The Ethical Implications of Generative AI in Content Marketing and Branding - Rahakbauw, Jessica Keisha; Barata, Fausta Ari (International Conference of Innovation and Community Engagement, 2025)
The rapid advancement of generative artificial intelligence (AI) technologies has transformed content marketing and branding by enabling automated creation of persuasive and personalized materials at scale. However, this innovation also raises critical ethical concerns related to authenticity, transparency, bias, and consumer manipulation. This study explores the ethical implications of using generative AI tools—such as GPT-based language models and AI-generated imagery—in the development of marketing content and brand narratives. Employing a qualitative research approach, data were gathered through in-depth interviews with digital marketing professionals, content creators, and AI ethicists, supplemented by case studies from leading global brands. The findings reveal that while generative AI offers significant efficiency and creativity benefits, it simultaneously presents risks of deceptive representation, erosion of consumer trust, data privacy violations, and the perpetuation of social biases. The study proposes a framework for ethical AI adoption in marketing, emphasizing the principles of transparency, informed consent, human oversight, and brand integrity. Additionally, it recommends the development of industry guidelines and regulatory mechanisms to ensure responsible use of generative AI in consumer-facing communication. This research contributes to the evolving discourse on AI ethics in marketing, offering actionable insights for practitioners, policymakers, and scholars navigating the balance between innovation and responsibility in the digital branding era.